2009
DOI: 10.1142/s0218625x0901272x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Observations of Orderly Structures in Copper Films Deposited on Liquid Substrates

Abstract: In this paper, an optical microscopy study of orderly structures, namely bands, which are observed in a nearly free sustained copper (Cu) film system, is presented. The band is composed of a large number of parallel key-formed domains with different width w but nearly uniform length L. This study shows that the morphologies of the Cu films are very susceptible to the deposition rate, i.e. with the increase in the deposition rate f , the bands with rectangular domains first become irregular gradually and then d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Silicone oil, being nonreactive and extremely stable under vacuum conditions (vapor pressure = 3 × 10 −10 mmHg), is appropriate for copper vapor deposition and growth. 36 The property of the sticking coefficient, which experimentally translates to the condensate-substrate energy was calculated via Density Functional Theory (DFT), it was found that copper atoms are weakly bound to the oxygen functional group (−0.55 eV), resulting in the low probability of oxidation from silicone oil. The binding energy with other functional groups was also found be relatively low (methyl −0.15 eV; silicon −1.09; hydrogen −0.55 eV), indicating minimal interaction between the condensing species and substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Silicone oil, being nonreactive and extremely stable under vacuum conditions (vapor pressure = 3 × 10 −10 mmHg), is appropriate for copper vapor deposition and growth. 36 The property of the sticking coefficient, which experimentally translates to the condensate-substrate energy was calculated via Density Functional Theory (DFT), it was found that copper atoms are weakly bound to the oxygen functional group (−0.55 eV), resulting in the low probability of oxidation from silicone oil. The binding energy with other functional groups was also found be relatively low (methyl −0.15 eV; silicon −1.09; hydrogen −0.55 eV), indicating minimal interaction between the condensing species and substrate.…”
Section: Resultsmentioning
confidence: 99%